Antibacterial and antioxidant activities of extracts from Calophyllum ferrugineum and Calophyllum incrassatum - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Deny Susanti, Darnis (2018)
Calophyllum is a pan-tropical genus belongs to the Guttiferae family and locally known in Malaysia as ‘bintangor’. There has been a continual interest to further investigate the phytochemistry of Calophyllum sp since this genus is a rich source of active secondary metabolites which showed anti-HIV, cytotoxicity and antimicrobial properties. In this study, antibacterial and antioxidant activities of barks and leaves of C. ferrugineum and C. incrassatum were investigated. Cold extraction method employing dichloromethane, ethyl acetate and methanol as solvent was performed. All extracts were tested for their total phenolic content and antioxidant activities by DPPH radical scavenging and Ferric Reducing Antioxidant Power (FRAP) assays. The methanol extract from the leaves of C. ferrugineum showed the highest TPC value at 122.08 mg GAE/g and the lowest DPPH SC50 value at 11.80 µg/mL. The methanol extract from the barks of C. ferrugineum was found to have the highest FRAP value among all extracts. The antibacterial activity of all extracts was tested by minimum inhibition concentration (MIC) test against Bacillus subtilis, Staphylococcus aureus, Escheria coli and Pseudomonas aeruginosa. Only the dichloromethane extract from bark of C. ferrugineum showed moderate MIC value against Gram positive bacteria, B. subtilis and S. aureus at 125 µg/mL.